A workflow for absolute quantitation of large therapeutic proteins in biological samples at intact level using LC-HRMS. (August 2016) - Jian, Wenying; Kang, Lijuan; Burton, Lyle; Weng, Naidong
Aim: The commonly used LC–MS workflow to quantify protein therapeutics in biological samples is 'bottom-up' approach. In this study, the aim is to establish 'top-down' approach for absolute quantitation of therapeutic antibodies or proteins of similar sizes in biological samples at intact level.Materials & methods : Using a recombinant human monoclonal antibody as the model molecule, we present a workflow to measure large therapeutic proteins in plasma at intact level based on deconvoluted high-resolution MS (HRMS) peaks. A novel MultiQuant™ software function was developed to automatically deconvolute the peaks and process the data.Results & conclusion: The workflow showed satisfying performance. This is a proof of concept study demonstrating the feasibility of bioanalysis of large therapeutic proteins at intact level using LC-HRMS.